HOW TEENAGERS PERCEIVE LANGUAGE AS A PART OF CULTURE: PROTOTYPE SEMANTIC APPROACH - Muhammad Hafiz Kurniawan; Syihabuddin Syihabuddin (BASIS (Bahasa dan Sastra Inggris), 2021)
Indonesia is known to have countless varieties of cultures because Indonesia consists of many tribes and languages. Bahasa Indonesia as the national language faces the new threat from the code mixing slang such as kids jaman now, mantap soul, unfaedah, and curigation which is so popular among the teenagers. This research aims to know the perspective of culture among the teenagers by using a semantic prototype which has a focus to know the grade of goodness. This semantic prototype in this research uses two methods in collecting the data, first is using free listing and the second is judging the examples of categorizations to evaluate which of the categories included as culture was positioned among others prototypically. The respondents of this research are 47 respondents for the first method and 52 respondents for the second method and their age range from 18-20 years old. The other questions are also asked to the respondents related to their knowledge about culture. The result of this research is that culture is seen to be something performable on stage such as traditional dance and costume, rites, and music and ironically language in this case is only in 6th position in the first method and 4th position in the second method. Although the position of language changes the acknowledgment of language as an integral part of culture is still low in number.